Absence of the RING domain in MID1 results in patterning defects in the developing human brain - Frank, Sarah; Gabassi, Elisa; Käseberg, Stephan; Bertin, Marco; Zografidou, Lea; Pfeiffer, Daniela; Brennenstuhl, Heiko; Falk, Sven; Karow, Marisa; Schweiger, Susann (Life Science Alliance, 2024)
The X-linked form of Opitz BBB/G syndrome (OS) is a monogenic disorder in which symptoms are established early during embryonic development. OS is caused by pathogenic variants in the X-linked gene MID1 Disease-associated variants are distributed across the entire gene locus, except for the N-terminal really interesting new gene (RING) domain that encompasses the E3 ubiquitin ligase activity. By using genome-edited human induced pluripotent stem cell lines, we here show that absence of isoforms containing the RING domain of MID1 causes severe patterning defects in human brain organoids. We observed a prominent neurogenic deficit with a reduction in neural tissue and a concomitant increase in choroid plexus-like structures. Transcriptome analyses revealed a deregulation of patterning pathways very early on, even preceding neural induction. Notably, the observed phenotypes starkly contrast with those observed in MID1 full-knockout organoids, indicating the presence of a distinct mechanism that underlies the patterning defects. The severity and early onset of these phenotypes could potentially account for the absence of patients carrying pathogenic variants in exon 1 of the MID1 gene coding for the N-terminal RING domain.
CRIS-Team Scopus Importer:2024-02-02

Unlocking the potential of SY-stem cells - Furlanetto, Federica; Frank, Sarah; Karow, Marisa (Development, 2024)
The sixth SY-Stem Symposium, jointly organized by the Research Institute of Molecular Pathology and the Institute of Molecular Biotechnology took place in Vienna in March 2024. Again, aspiring new group leaders were given a stage to present their work and vision of their labs. To round up the excellent program, the scientific organizers included renowned keynote speakers. Here, we provide a summary of the talks covering topics such as early embryogenesis, nervous system development and disease, regeneration and the latest technologies.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Early embryogenesis; Organoids; Single cell technologies; Stem cells